ANALISIS MISKONSEPSI MAHASISWA PGSD DENGAN METODE CERTAINTY OF RESPONSE INDEX (CRI) MELALUI FITUR QUIS EDMODO - Tri wiyoko; Puput Wahyu Hidayat (Jurnal Muara Pendidikan, 2020)
The problem of this research is the finding of wrong conceptual understanding by students on vibration and wave material. Wrong understanding of the concept results in misconceptions in cognitive aspects, scientific attitudes and student skills. This study aims to analyze student misconceptions with the Certainty Of Response Index (CRI) model through the edmodo quis feature. The subjects of this research were students of the PGSD STKIP MB Study Program for the 2019/2020 Academic Year. This type of research is qualitative research using descriptive methods. Furthermore, the research instrument used an objective test instrument. The results of this study are in the form of evaluation test kits that have been validated from the aspects of the content of the material and language by the experts. The results of the validation of the material content aspect were 93.75% in the very good category, the question construction aspect was 96.42% in the very good category and the language aspect was 90.6% with the very good category. This shows that the question has the feasibility of being applied. The test results showed that the misconceptions experienced by students regarding the wave material were very diverse. The average student misconception on vibration and wave material was 23.17% with the low category.